1986
DOI: 10.1128/aac.30.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect ampicillin-resistant, non-beta-lactamase-producing Haemophilus influenzae by standard disk susceptibility testing

Abstract: We questioned whether the apparent rarity of ampicillin-resistant, non-4-lactamase-producing (NBLP) Haemophilus influenzae was due to failure of detection. We identified ampicillin-resistant and ampicillinsusceptible H. influenzae by the agar dilution technique, using 105-and 103-CFU inocula. We compared the disk susceptibility of 18 ampicihlin-resistant NBLP strains, 13 ampicillin-resistant, (8-lactamase-producing strains, and 10 ampicillin-susceptible strains by using standard 10-and 2-,ug ampicillin disks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 35 publications
0
25
2
Order By: Relevance
“…Table 1 shows the amoxicillin and amoxicillin-clavulanate MICs for the three phenotypic groups tested. Although no overlap was observed between Amps and Amp'NBLP strains, MICs for two of the latter strains were 1 ,ug/ml with HTM media, whereas previously MICs for all strains were .1.5 ,ug/ml at the lower inoculum of 103 CFU when tested on sBHI agar (15). AmprBLP strains with the other antibiotics tested (amoxicillin-clavulanate, cefaclor, cefuroxime, ceftriaxone, and cefotaxime).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the amoxicillin and amoxicillin-clavulanate MICs for the three phenotypic groups tested. Although no overlap was observed between Amps and Amp'NBLP strains, MICs for two of the latter strains were 1 ,ug/ml with HTM media, whereas previously MICs for all strains were .1.5 ,ug/ml at the lower inoculum of 103 CFU when tested on sBHI agar (15). AmprBLP strains with the other antibiotics tested (amoxicillin-clavulanate, cefaclor, cefuroxime, ceftriaxone, and cefotaxime).…”
Section: Methodsmentioning
confidence: 99%
“…P-Lactamase production was determined by incubating suspensions of each strain with 3-lactamase substrate (chromogenic cephalosporin; Calbiochem-Behring, La Jolla, Calif.) at room temperature for 30 min and visually assessing color development. The Ampr NBLP strains were identified previously (15,16), with ampicillin MICs of .1.5 jig/ml in comparison to Amps isolates, for which MICs were -0.5 ,ug/ml. All 18 susceptible strains were nontypable, with the site of isolation as follows: 10 respiratory tract, 5 eye, 1 ear, 1 ATCC 33391, and 1 site unknown.…”
Section: Methodsmentioning
confidence: 99%
“…However, little has been documented regarding beta-lactamase-negative, ampicillin-resistant isolates. The limited evidence which exists suggests that these isolates are less influenced by inoculum than are the beta-lactamase-producing strains (68). Results may vary sufficiently to warrant the testing of a higher inoculum.…”
Section: Effect Of Inoculum Sizementioning
confidence: 99%
“…Mendelman et al (68) reported that 8 of 18 ampicillinresistant strains which lacked beta-lactamase were classified as falsely susceptible by the NCCLS guidelines. They proposed the use of a 2-itg ampicillin and 2-pug ampicillin/10-pug clavulanic acid disk as an alternative method for classifying resistant and susceptible strains.…”
Section: Effect Of Inoculum Sizementioning
confidence: 99%
See 1 more Smart Citation